Subjetivação em Queda Livre: imagens da cibercultura em Black Mirror - Genuíno, Renata Reis (2020)
The aim of the research was to discuss and analyze aspects of subjectivation in cyberculture through the logic of the production of desire placed in the acts of sharing and liking images on virtual platforms. For this purpose, it was realised the filmic interpretation of the episode “Nosedive” of the series “Black Mirror”. The method of reading and understanding the scenes was carried out through the selection of images captured from the episode, in which the cut-outs of (and with) the series are handled under the notion of Planks, addressing the lacunae aspects of the images in the context of virtual classification, that modifies the machine-body relationship put in sharing the image. The discussion of the scenes, in relation to the images of the world, revealed the subjectivation under its aspect of constant variation through virtual encounters and the crossings of cyberculture in the production of desire.